A Whole-child, whole-family approach to health assessments for asylum-seeking children. (24th November 2022) - Sanchez Clemente, Nuria; Cinardo, Paola; Ward, Allison; Longley, Nicky; Harkensee, Christian; Eisen, Sarah
Abstract : In 2020, 21% of people who sought asylum in the UK were children. This population has complex interconnecting health and social needs. Assessment requires a holistic approach, with consideration of physical and mental health in addition to social and developmental well-being, within the whole family group. A trauma-informed life-cycle and intergenerational care approach is important. This article, aimed at all health professionals who may work with asylum-seeking families, outlines the best practice principles for undertaking health assessments in migrant children and young people.